Структура и износостойкость хромомарганцевого наплавленного металла - Малинов, В.Л.; Малинов, Л.С. (Автоматическая сварка, 2012)
Приведены результаты исследований структуры и износостойкости наплавленного порошковыми лентами низкоуглеродистого металла различных структурных классов, содержащего примерно 13 % хрома и от 2 до 12 % марганца. Исследована возможность повышения износостойкости наплавленного металла за счет последующих после наплавки отпуска и цементации. Показано, что получение в структуре наплавленного металла наряду с мартенситом оптимального количества метастабильного аустенита повышает его износостойкость. Results of investigation of the structure and wear resistance of low-carbon metal of various structural classes deposited with flux-cored strips, containing approximately 13% chromium and different amounts of manganese (from 2 up to 12 %), are given. Possibility of increasing the deposited metal wear resistance due to tempering and carbonizing after surfacing, was studied. It is shown that obtaining the optimum quantity of metastable austenite in the deposited metal structure, alongside with martensite, improves its wear resistance.